Application of the STAD Type Cooperative LearningModel with the SETS Approach to Student LearningOutcomes at Arosbaya Middle School - Nurul Fitria Ningsih (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to describe the implementation of the STAD type cooperativelearning model with the SETS approach, student learning outcomes, and studentresponses after participating in the teaching and learning process. This type ofresearch is pre-experimental, using one class as the research target, namely classVIII-i with 34 students. The research design used is a one shot case study design. Theresearch was carried out over three meetings, with two meetings for the teachingand learning process, and one meeting for tests on students' cognitive andpsychomotor learning outcomes. The observation results show that theimplementation of the STAD type cooperative learning model with the SETSapproach on household chemicals material has been managed according to syntaxin the very good category (89%). The learning outcomes for the cognitive aspecthave successfully completed 30 students (88.2%), while 4 students (11.8%) did notcomplete it. Based on the results of the normality test, it was found that the classhad a normal distribution with χcount<χtable (9.5<11.07) with α=0.05. Based on theone-party t test, it was found that tcount > ttable (α=0.05), with tcount of 4.96 andttable of 1.70. This shows that the application of the STAD type cooperative modelwith the SETS approach to household chemicals material can improve studentlearning outcomes. Students' performance skills observed through thepsychomotor aspect showed the very good category (90.8%) and the affectiveaspect showed the good category (84.5%). Based on the results of thequestionnaire, it is known that students responded positively to the learning thattook place with very good criteria (95.3%).